Thinking outside the box : a contemporary television genre reader - Edgerton, Gary R. (Gary Richard), 1952-; Rose, Brian Geoffrey (University Press of Kentucky, 2005)
'Thinking Outside the Box' brings together some of the most challenging scholarship about TV genres, exploring their genesis, functions and development, and the interaction of disparate genres.